The role of game methods in increasing students' interest in drawing - Eshmurodov Axmadjon Nurmuradovich (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Annotation: This article explores the role and effectiveness of game-based methods in teaching the subject of drawing. The research focuses on how game technologies stimulate students’ motivation, enhance their creative abilities, and foster independent and analytical thinking. The implementation of game elements in the educational process makes it more engaging, interactive, and accessible for students. The article also discusses the pedagogical mechanisms of applying game-based learning in drawing lessons, its didactic purposes, and its impact on developing students’ graphic literacy and spatial thinking. Experimental results and theoretical analysis confirm that game-based methods significantly increase students’ interest in the subject and improve learning outcomes.